Antibacterial Effects of Ethanolic Extract of Bidara (Ziziphus mauritiana Lam) Leaf Against Porphyromonas gingivalis - Noor Aziza; Islamy Rahma Hutami; Recita Indraswary; Suryono Suryono (Universitas Muhammadiyah Yogyakarta, 2022)
The bidara plant (Ziziphus mauritiana Lam) is widely distributed in various Asian countries. Bidara leaves contain secondary metabolites, the main content of which is flavonoids. As a gram-negative anaerobic bacteria, Porphyromonas gingivalis is one of the normal flora of the oral cavity. However, over quantities of this bacteria can promote chronic periodontitis. This research aims to analyze the bidara leaf ethanolic extract as an inhibitory agent of Porphyromonas gingivalis. This research design is experimental laboratory research with a post-test controlled group of Porphyromonas gingivalis inhibition. A total of 25 samples consisted of 5 groups of ethanol extract of bidara leaves at concentrations of 1%, 3%, 9%, positive control betel leaves, and negative control aquadest. Bacteria incubation was held for 48 hours, and the free bacterial zone was analyzed by the One Way ANOVA test. The results of the analysis showed that there was a significant difference between the control group and the treatment group. This study concludes that the ethanol extract of bidara leaves had a strong inhibitory effect on Porphyromonas gingivalis.